2015
DOI: 10.4103/0976-237x.152959
|View full text |Cite
|
Sign up to set email alerts
|

Multiple jaw cysts-unveiling the Gorlin-Goltz syndrome

Abstract: Gorlin-Goltz syndrome or basal cell nevus syndrome is a comparatively rare syndrome characterized by basal cell nevi, odontogenic keratocysts, and skeletal anomalies. Diagnosis is based on the major and minor clinical and radiographic criteria. Dentist plays a major role in the diagnosis of this disease due to the oral and maxillofacial manifestations of the syndrome. In some cases, jaw cysts are diagnosed by routine radiographs advised by the dentists. Odontogenic keratocysts in such syndromic patients will b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
0
14
0
4
Order By: Relevance
“…Gorlin syndrome, also known as Gorlin-Goltz syndrome (GGS), nevoid basal-cell carcinoma syndrome (NBCCS), jaw cysts syndrome or fifth phakomatosis, is a rare genetic disease of autosomal dominant inheritance. Mutation of human Patched gene PTCG1 is responsible for the occurrence of the disease [1,2,3]. The gene is located on chromosome 9 (q22-q31) and its most likely position is between D9S12 and D9S53 DNA markers.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gorlin syndrome, also known as Gorlin-Goltz syndrome (GGS), nevoid basal-cell carcinoma syndrome (NBCCS), jaw cysts syndrome or fifth phakomatosis, is a rare genetic disease of autosomal dominant inheritance. Mutation of human Patched gene PTCG1 is responsible for the occurrence of the disease [1,2,3]. The gene is located on chromosome 9 (q22-q31) and its most likely position is between D9S12 and D9S53 DNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…The gene is located on chromosome 9 (q22-q31) and its most likely position is between D9S12 and D9S53 DNA markers. Although its occurrence among family members is an important diagnosing criterion, it has been found that between 20-40% of cases result from a de novo mutation of the PTCH1 gene [1,4,5]. According to some researchers, new mutations occur in 35-50% of patients [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations